The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12859-016-1366-1
|View full text |Cite
|
Sign up to set email alerts
|

PARRoT- a homology-based strategy to quantify and compare RNA-sequencing from non-model organisms

Abstract: BackgroundNext-generation sequencing promises the de novo genomic and transcriptomic analysis of samples of interests. However, there are only a few organisms having reference genomic sequences and even fewer having well-defined or curated annotations. For transcriptome studies focusing on organisms lacking proper reference genomes, the common strategy is de novo assembly followed by functional annotation. However, things become even more complicated when multiple transcriptomes are compared.ResultsHere, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In the past decades, accompany with the fast innovation and development of sequencing technique, many important progression have been achieved [ 12 , 13 ]. High-throughput sequencing and bioinformatics analysis powerfully assist the non-coding RNA research on the epigenetic modification, discovering huge amounts of new identified functional lncRNAs in tumorigenesis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, accompany with the fast innovation and development of sequencing technique, many important progression have been achieved [ 12 , 13 ]. High-throughput sequencing and bioinformatics analysis powerfully assist the non-coding RNA research on the epigenetic modification, discovering huge amounts of new identified functional lncRNAs in tumorigenesis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were also made to identify potential transcription factors, CYP450s and UGTs that play a key role in regulation and diversification of secondary metabolites. Paired-end sequencing strategy extends the mapped fragment length to 200–500 bp so it is expected to be useful in obtaining longer reads, allows for detecting alternate splice junctions, deletions, insertions, and is useful for de novo transcriptome assembly [ 28 ]. Transcripts generated after assembly were functionally elucidated in different gene ontology, some of the secondary metabolic pathway related transcripts were selected for further validation.…”
Section: Introductionmentioning
confidence: 99%
“…The latter requires less memory than BBb as the partial digestion problem is solved in two stages in breadth-first mode. Gan et al [5] have developed a comparative transcriptomic analysis webserver, PARRoT, for non-reference organisms, using a homologue-based virtual transcriptome reference, which provided homologues from sequence databases as well as gene ontology (GO) terms. For entire microbial communities, Xie et al [6] have developed RiboTagger, for fast and accurate recovery of small subunit ribosomal RNA sequences, from all three domains of life.…”
Section: Sequence Analysis and Ontologiesmentioning
confidence: 99%